Expression of carboxylesterase and paraoxonase in the placenta and their association with chlorpyrifos exposure during pregnancy - Rodriguez, Piuque M. (2025)
Exposure to environmental chemicals during pregnancy, including organophosphate pesticides, can affect the health of both the mother and the fetus, and have repercussions later in life. The present study aimed to determine whether the A-esterases paraoxonases (PON) and the B-esterases carboxylesterases (CES) are modulated in the placenta of pregnant women residing in an intensive pesticide use scenario. A total of 104 healthy pregnant women were recruited between 2018 and 2022 and were classified according to their residential settings in rural (RG) and urban (UG) groups. Chlorpyrifos (CP) level in the placenta was determined by GC-ECD, and confirmed by GC-MS. To analyze possible impacts in esterases, the CES and PON activity, mRNA transcript and protein expression levels were studied. Significantly higher CP levels were detected in RG vs UG. Also, CES activity determined with 1-naphthyl acetate substrate was significantly lower in RG vs UG. In contrast, PON arylesterase and lactonase activities were up modulated in RG vs UG. Likewise, mRNA transcript levels of CES1, CES2 and PON2 were upregulated in the RG along with increases in CES2 and PON2 protein expressions. Moreover, a positive significant correlation was determined between CP concentration and CES1 and CES2 mRNA levels. Rural samples showed elevated CP concentrations and alterations in esterases, which elucidate the impact of CP exposure in mRNA CES and PON regulation. These findings highlight the need for further investigation into the effects of pesticide exposure during pregnancy and to deepen the knowledge about the function that esterases play in the placenta.